Dissecting eustachian tube dysfunction: From phenotypes to endotypes. - Cuneyt M Alper; Miriam S Teixeira; Ellen M Mandel; J Douglas Swarts (PLoS ONE, 2023)
Objective A broad spectrum of complaints, symptoms and manifestations has been assigned to Eustachian tube (ET) dysfunction (ETD). While such presentations may manifest as ETD phenotypes, underlying mechanisms are defined as endotypes. Our goal is to develop a diagnostic approach to differentiate the endotypes and guide clinicians in the workup and selection of treatments targeting the mechanism of ETD. Study design Retrospective. Setting Tertiary care. Subjects and methods Children and adults with suspected ETD were evaluated with a thorough examination, otomicroscopy, otoendoscopy, trans-nasal videoendoscopy and testing of passive and active ET dilatory properties. Degree of weakness in soft palate elevation and ET orifice widening (muscular weakness, ETD-M), presence of inflammation (ETD-I) and/or adenoid tissue impinging and restricting the ET opening (ETD-R) were assessed with video-endoscopy. The Forced Response Test, Inflation-Deflation Test and Pressure Chamber Test were used as applicable to quantify the degree and type of difficulty (Stricture, ETD-S or adhesive, ETD-A) or ease (patulous or semi-patulous, ETD-P/SP) in opening the ET, and degree of active muscular strength/weakness (ETD-M) was measured. Ears with normal function (ETF-N) findings were also identified. Results Video-endoscopic and ETF test results were obtained for 71 ears of 40 subjects (22 males, 18 females; 38 white, 2 black), with an average age of 22.9 ± 16.5 years (min:6.2, max:64.1). Videoendoscopy (21, 13, 33, 16, 13, 0, 0 ETs) and ETF testing analysis (20, 24, 0, 38, 0, 3, 13 ears) were categorized as ETF-N and the ETD endotypes ETD-S, ETD-R, ETD-M, ETD-I, ETD-A, and ETD-P/SP, respectively. Some phenotypes had features consistent with more than one endotype. Conclusion A systematic approach of examination and testing may differentiate the specific underlying mechanisms, lead to a treatment targeted to the ETD endotype and may establish novel ways to diagnose and treat ETD.